Pengaruh Penerapan Model Flipped Learning dan Motivasi Belajar Terhadap Hasil Belajar Siswa - Rani Sahara; Rani Sofya (Jurnal Ecogen, 2020)
This study aims to reveal the effect of applying the learning model and learning motivation on student learning outcomes. This type of research used a quantitative approach, especially quasi-experiments. Population in this study all students of class XI 2 Painan. The sampling technique is purposive sampling. The sample in this study amounted to 63 students. Data analysis techniques used questionnaires and tests. Data analysis techniques used were descriptive analysis, normality test, homogeneity test, and hypothesis testing. The results of this study indicate that: (1) Differences in learning outcomes obtained between students who have high learning motivation in class who apply the flipped learning model (2) Differences in learning outcomes obtained between students who have low learning motivation in the class applying conventional models (3) Differences learning outcomes obtained between students who have high learning motivation in the class implementing the flipped learning model and students who have high learning motivation in the class applying conventional models (4) Differences learning outcomes obtained between students who have low learning motivation in the class implementing the flipped learning model and students who have low learning motivation in the class applying conventional models (5) There is no interaction between learning models and learning motivation in influencing learning outcomes.Keywords : flipped learning model, learning motivation, learning outcomes